Interactive biology media learning development to the student learning style (audio-visual-kinesthetic) based on Google Site - Rahmat Dzulfikry; Patta Bundu; Syukur Saud (Universal Teaching and Learning Journal, 2025)
Purpose: This research aims to develop interactive learning media based on Google Sites tailored to students’ learning styles, including visual, auditory, and kinesthetic, in order to improve learning outcomes in junior high school biology. Methods: This study used a Research and Development (R&D) approach with the 4D model (define, design, develop, disseminate). Instruments included expert validation sheets, practicality questionnaires, and pre-test and post-test questions. Data were analyzed using descriptive validation, practicality results, and the N-Gain test to measure effectiveness. Results: The results showed that media expert validation scored 80%, material expert validation also 80%, and teacher validation 80%, all categorized as valid and requiring no revision. Student responses indicated positive perceptions: 100% found the media easy to understand and 80.9% found it visually attractive. The N-Gain score was 56.29%, categorized as “quite effective,” with average student achievement increasing from 70.47 (pre-test) to 87 (post-test), showing significant improvement in learning outcomes. Conclusion: Google Site-based interactive learning media is valid, practical, and quite effective in supporting biology learning. Its application can increase students’ enthusiasm, understanding, and outcomes in the Human Digestive System topic. Limitation: The research was limited to one school (SMP Insan Scholar Madani BSD), one subject (biology), and one topic (digestive system), so generalizability is limited. Dissemination was also limited to biology teachers at the same school. Contribution: This study provides a practical model for integrating technology-based interactive media aligned with students’ learning styles. It enriches literature on digital learning tools in Indonesian secondary education and offers a reference for teachers and researchers developing similar media.